THE USE OF SHRINKING STORY IN TEACHING SPEAKING OF SMP NEGERI 06 PONTIANAK - Rahmiyati, .; Suhartono, Luwandi; Husin, Syarif (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis research purpose is to investigate the effect size of teaching speaking narrative monologue by using shrinking story strategy at the eighth grade students in SMP Negeri 06 Pontianak. The method that is used in this research is pre-experimental method that applies pre-test and post-test to measure the effect size (ES) of the treatment. The instrument of this research are pre-test and post-test. Both pre-test and pre-test measure studentsâ€™ speaking narrative monologue performance. The pre-test was applied before the treatment was given. Meanwhile the post-test was applied after the treatment given. The different score of pre-test and post-test are respectively 2.10 and 2.87. The result shows that the effect size of teaching speaking narrative monologue by using shrinking story strategy is high because the Effect Size (ES) is > 0.5. The shrinking story strategy is higly effective to teach speaking narrative monologue to the eighth grade students in SMP Negeri 06 Pontianak. This research result can be applied to teach speaking narrative monologue concerns to standard competence 4. Basic competence of KTSP point 4.2. Expressing meaning in simple monologue speaking with spoken language accurately in daily context in form of recount, narrative and procedure.Â Keyword: Pre-Experimental, Speaking, Teaching, Shrinking Story